Part-time and full-time medical specialists, are there differences in allocation of time? - Groenewegen Peter P; Heiligers Phil; de Jong Judith D; Hingstman Lammert (BMC, 2006)
Abstract Background An increasing number of medical specialists prefer to work part-time. This development can be found worldwide. Problems to be faced in the realization of part-time work in medicine include the division of night and weekend shifts, as well as communication between physicians and continuity of care. People tend to think that physicians working part-time are less devoted to their work, implying that full-time physicians complete a greater number of tasks. The central question in this article is whether part-time medical specialists allocate their time differently to their tasks than full-time medical specialists. Methods A questionnaire was sent by mail to all internists (N = 817), surgeons (N = 693) and radiologists (N = 621) working in general hospitals in the Netherlands. Questions were asked about the actual situation, such as hours worked and night and weekend shifts. The response was 53% (n = 411) for internists, 52% (n = 359) for surgeons, and 36% (n = 213) for radiologists. Due to non-response on specific questions there were 367 internists, 316 surgeons, and 71 radiologists included in the analyses. Multilevel analyses were used to analyze the data. Results Part-time medical specialists do not spend proportionally more time on direct patient care. With respect to night and weekend shifts, part-time medical specialists account for proportionally more or an equal share of these shifts. The number of hours worked per FTE is higher for part-time than for full-time medical specialists, although this difference is only significant for surgeons. Conclusion In general, part-time medical specialists do their share of the job. However, we focussed on input only. Besides input, output like the numbers of services provided deserves attention as well. The trend in medicine towards more part-time work has an important consequence: more medical specialists are needed to get the work done. Therefore, a greater number of medical specialists have to be trained. Part-time work is not only a female concern; there are also (international) trends for male medical specialists that show a decline in the number of hours worked. This indicates an overall change in attitudes towards the number of hours medical specialists should work.